Liver traumatisms - Valls, Alberto (Cirugía del Uruguay, 1976)
The authors consider liver injuries a dramatic problem which has not yet been totally solved. Their prognosis has improved with intensive reanimation treatment and should improve even more with. adequate surgery. Far this purpose it is essential to have correct approach, exploration, and treatment of hepatic lesions (mainly centered on resections, since the liver has terminal type circulation) aided by arteriography, cholangiography and gammagraphy. A good temporary hemostasis of the hepatio pedicle. and cava! vein, with drainage of the biliary tract through the gall bladder, the common hile duct or a segmentary duct is required. It is also necessary to have correct drainage of the perihepaiic spaces and the peritoneum.